Faktor-Faktor Yang Mempengaruhi Minat Anak Petani Dalam Melanjutkan Usahatani Di Desa Curug Kecamatan Klari Kabupaten Karawang - Bahari, Reza; Abubakar, Abubakar; Azzahra, Fatimah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Interest is a tendency that persists in an individual to pay attention to and follow a desire. Interest is a tendency for someone who is sedentary to feel interested and happy in a particular field or thing. Interest has a big influence on the activities a person will do. Interest in activities makes a person do an activity with pleasure and attention. The problem in Curug Village is that there is no youth interest in continuing family farming in Curug Village, which causes lagging behind in the agricultural sector, and many young people choose to work in private companies rather than working as farmers. This study aims to analyze the interest of youth in continuing farming in Curug Village and whether factors influence youth interest in farming in Curug Village. The research was conducted in Curug Village, Klari District, and Karawang Regency. The population in this study were young farmers in Curug Village, with 24 respondents. The method used was a census or sample. The results of this study show that the interest of farmer children in continuing farming in Curug Village is high at 69,58%. Emotional variable factors do not have a major effect on the interest of farmer children in continuing farming with a percentage of 50.7%; environmental variable factors do not affect the interest of farmer children in continuing farming with a percentage of -42.3%; and socioeconomic variable factors affect the interest of farmer children in continuing farming with a percentage of 56.0%.